2021
DOI: 10.1111/jsr.13358
|View full text |Cite
|
Sign up to set email alerts
|

Sleep structure and electroencephalographic spectral power of middle‐aged or older adults: Normative values by age and sex in the Korean population

Abstract: The fine structure of sleep electrocortical activity reflects health and disease. The current study provides normative data for sleep structure and electroencephalography (EEG) spectral power measures derived from overnight polysomnography (PSG) and examines the effect of age and sex among Korean middle‐aged and older adults with or without obstructive sleep apnea (OSA). We analysed home PSG data from 1,153 adult participants of an ongoing population‐based cohort study, the Korean Genome and Epidemiology Study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 76 publications
(87 reference statements)
0
10
1
Order By: Relevance
“…In the present study, we examined the bidirectional associations between physical activity and both objective and subjective sleep quality in older adults. Our analysis revealed that the characteristics of stage N3 sleep were better among our participants than among those included in a previous epidemiological study 28 . In 80% of younger adults, changes in sleep structure related to stage N3 appear within approximately 1 h after falling asleep 34 ; however, such changes occurred in only 20% of older adults in the current study (Fig.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…In the present study, we examined the bidirectional associations between physical activity and both objective and subjective sleep quality in older adults. Our analysis revealed that the characteristics of stage N3 sleep were better among our participants than among those included in a previous epidemiological study 28 . In 80% of younger adults, changes in sleep structure related to stage N3 appear within approximately 1 h after falling asleep 34 ; however, such changes occurred in only 20% of older adults in the current study (Fig.…”
Section: Discussioncontrasting
confidence: 45%
“…Some previous studies have attempted to achieve more accurate quantitative and qualitative evaluations based on estimated sleep stages and delta power (0.75–4.00 Hz) 27 , 28 . Delta power refers to the scalp surface representation of a highly complex ensemble of oscillatory activity during non-REM sleep, including the cortical up and down states that comprise the slow oscillation 29 , 30 .…”
Section: Introductionmentioning
confidence: 99%
“…Beta band) 24 . With healthy ageing, previous reports have shown that Delta power decreases and Alpha and Sigma power increase, indicating that sleep becomes lighter with age 25 , 26 . In insomnia disorder, a recent meta-analysis reported increased Alpha, Sigma and Beta power and lower Delta power compare to healthy adults, notably during NREM sleep 27 .…”
Section: Introductionmentioning
confidence: 90%
“…the likely benefit of an increased length and intensity of their SWS, at least until they reach menopause (Choi et al, 2019;Roehrs et al, 2006;Yoon et al, 2021). Although the percentage of SWS and the slow-wave activity power markedly decrease in both men and women as they get older, the sleep of men is characterised by a steeper decline in these measures and a higher arousal index (Baker et al, 2016;Mallampalli & Carter, 2014;Moraes et al, 2014;Redline et al, 2004;.…”
Section: Objective Assessments Of Sleepmentioning
confidence: 99%
“…In terms of spindle characteristics, women's fast sleep spindles typically display greater density and enhanced oscillations compared to men's (Choi et al, 2019; Merikanto et al, 2017; Ricci, He, Calhoun, et al, 2021). Spectral analyses show that absolute rather than relative spectral power varies by sex, with women showing greater power densities across all frequency bands, except for Beta power, throughout the night (Yoon et al, 2021). Relative power in Alpha, Beta and Sigma ranges is higher in adult women, which has been linked to insomnia symptoms and may better account for sex‐specific anatomical variations (e.g., head size, skull, or skin thickness) (Choi et al, 2019).…”
Section: Sex and Sleepmentioning
confidence: 99%